2021
DOI: 10.1111/ffe.13481
|View full text |Cite
|
Sign up to set email alerts
|

An improved fatigue damage model based on the virtual load spectrum of golden section method

Abstract: This paper presents an improved damage model based on the construction technology of nonlinear partition virtual load spectrum by golden section method which is closer to the actual condition. In contrast to the Palmgren–Miner classical model, the result of fatigue life is more accurate. The improved damage model uses reliability instead of cumulative fatigue damage as the fatigue failure criterion. The objectives in this paper include verifying the convergence of the improved model and analyzing the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These intervals are defined by the upper and lower boundary values of max j C and min j C . The improved golden section method is used to determine the five standard cloud eigenvalues, taking into account expert scoring habits 51 . He value of 0.1, the specific values of the 2D standard cloud were calculated using Equation ( 21)-Equation ( 23) and are presented in Table 7.…”
Section: W W W Ex En Hementioning
confidence: 99%
“…These intervals are defined by the upper and lower boundary values of max j C and min j C . The improved golden section method is used to determine the five standard cloud eigenvalues, taking into account expert scoring habits 51 . He value of 0.1, the specific values of the 2D standard cloud were calculated using Equation ( 21)-Equation ( 23) and are presented in Table 7.…”
Section: W W W Ex En Hementioning
confidence: 99%
“…Based on the increasing theoretical research on CCF fatigue damage accumulation in turbine blades, some fatigue life prediction models under CCF loading conditions have been proposed. [42][43][44][45][46][47][48][49][50][51] For instance, based on damage mechanics theory, Han et al 48 proposed a life prediction model for CCF. The prediction model has been verified by experimental results, and a method for determining the allowable aluminized position in turbine blades is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers have focused on the CCF life prediction model. Based on the increasing theoretical research on CCF fatigue damage accumulation in turbine blades, some fatigue life prediction models under CCF loading conditions have been proposed 42–51 …”
Section: Introductionmentioning
confidence: 99%
“…Investigation of surface roughness and slip rate on contact fatigue life. Zaretsky [24][25][26][27][28][29] 's study showed that surface roughness of parts would affect the distribution of surface contact stress, which would lead to the phenomenon of contact stress concentration of parts and increase the wear amount of parts surface. Ne'lias et al 30 evaluated the influence of inclusions, surface roughness, and operating conditions on rolling contact fatigue of AISI 52100 and M50 bearing steels, and studied the influence of inclusion location and roughness size on crack initiation and propagation life.…”
Section: Introductionmentioning
confidence: 99%